PELAKSANAAN PENGAWASAN OLEH KPPBC TMP C SABANG TERHADAP LALU LINTAS BARANG DARI PELABUHAN BEBAS SABANG - Fachrurrazi Idram; Mohd. Din; Efendi Efendi (Universitas Islam Negeri Ar-Raniry, 2018)
Sabang area has become a separate area of customs area so free from imposition of import duties, value added tax, sales tax on luxury goods and excise duty. To that end, the Direktorat Jenderal Bea dan Cukai (DJBC) shall supervise the importation and release of goods to and from and located in Sabang area. In the period from March 2013 to October 2017 there have been 88 cases of customs violations related to freight traffic from Sabang Free Port to other places within the Customs Area, especially in the supervision of the Kantor Pengawasan dan Pelayanan Bea dan Cukai (KPPBC) of Sabang. The main problem of this study is why the implementation of surveillance of goods traffic by DJBC to goods traffic in Sabang Free Port has not been running optimally, what are the obstacles that cause the implementation of surveillance of goods traffic from Sabang Free Port so it has not run well and whether the effort should do. The method used in this research is empirical law research method. The result of the research explains that DGCE monitoring through KPPBC Sabang against goods traffic in Customs Area is not optimal due to unavailability of system based information access, lack of adequate facilities and infrastructure, lack of cooperation agreement with other institutions, Human Resources (HR), as well as the vast area of supervision. Efforts are made by requesting the procurement of information technology systems, requests for additional HR, improvement ofinfrastructure facilities, the procurement of several monitoring posts and so forth.